Modelling of 132kV overhead transmission lines by using ATP/ EMTP for shielding failure pattern recognition - Nur Zawani, Saharuddin; Junainah, Leman; Imran, Sutan Chairul; Mohd Faizuhar, Razali (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.